DETEKSI PENYEBARAN BAKTERI Aeromonas hydrophilla PADA IKAN LELE DUMBO (Clarias gariepinus) DI KECAMATAN MEDAN TUNTUNGAN - Rahmad Hidayat; Pindi Patana; Indra Lesmana (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2014)
Aquaculture of Catfish has several advantages, such as rapid growth, high ability to adapt in environmental, and high nutritional content. Nowdays, most of the African catfish aquaculture used intensive farming systems. One of important factor for catfish aquaculture pests and diseases. Disease problems are usually a major obstacle because it can harm aquaculture such as total mortality, productivity and in water quality. One of the diseases that often attack the catfish is A. hydrophila bacterium. This research had been conducted on September – November 2013. This reseach intend to identify and determine spreading of the bacterium A. hydrophila in catfish especially in Medan Tuntungan Sub-district. This research used sampling method, bacterial diagnosis and identification of bacteria. The result showed, from 90 isolates, 19 of them infected by A. Hidrophila bacteria, that was 7 species in pond I, 0 species in pond II, 7 species in pond III, 3 Species in pond IV, 2 species in pond V.Keyword : Cathfish (Clarias batrachus), Bacteria Identify, Types of Bacterias, Aeromonas hydrophila Bacterium.